Informational value of challenging an incumbent prosecutor. (27th August 2021) - McCannon, Bryan C.
Abstract: Popular elections are used to select prosecutors in most U.S. states. It has been questioned whether voters have the knowledge or incentive to identify quality individuals. In 2011, New York State instituted a series of salary increases for judges. Prosecutors' salaries are tied to judicial compensation by law so that an exogenous shock arose. I develop a simple asymmetric information model where a better informed insider can choose to contest the incumbent. Theory predicts that if voters are updating beliefs in a sophisticated manner, then in equilibrium there is not a change in the rate at which incumbents are challenged. When they are challenged, though, incumbents receive more electoral support. Results from the quasi‐natural experiment are consistent with the theory. The incumbent's vote margin grows by 6 percentage points after the salary increase and the probability an incumbent wins a contested re‐election increases by 33%.